Population structure of Iberian honey bees: concordance among mtDNA, geometric morphometrics and SNPs - Pinto, M. Alice (2018)
No other honey bee subspecies has caught so much attention from evolutionary biologists as Apis mellifera iberiensis. For over 25 years, Iberian honey bee populations have been surveyed using a wide range of markers, including morphometry, allozymes, mtDNA, microsatellites, and more recently SNPs. Despite the numerous studies, diversity patterns of Iberian honey bees are still not fully dissected and understood. In this study we performed a ﬁne-scale sampling at both geographical and genomic level. Samples from over 711 colonies were collected across three north-south transects. These samples were sequenced for the mitochondrial tRNA"“-cox2 intergenic region, scored using geometric morphometrics of forewings, and genotyped for over 383 SNP loci. The three sets of markers concurrently supported the existence of a north-south cline, a pattern that contrasts with the absence of structure inferred from microsatellites. To test the hypothesis that selection has shaped and maintained the nuclear cline, we employed four PST-based outlier methods on the SNP data set. These analyses enabled detection of 74 outlier loci, which supports the selection hypothesis. However, neutral structure, inferred following removal of outliers, was able to recapture the north-south cline, which suggests that selection is not the only evolutionary force shaping the Iberian cline. Our ﬁndings further highlight the complexity of the Iberian honey bee diversity patterns and reinforce the importance of this southernmost European territory as a reservoir of Apis mellifera genetic diversity, a resource increasingly important in a rapidly changing and demanding world.